Research studies on educational technology appearing in journal of education: A case study of Mahasarakham university - Singporn, Rungthip (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to synthesize research studies on educational technology published in the Journal of Education Mahasarakham University during the year 2016-2020. The samples used in this study were 34 published research articles on educational technology. Research articles were analyzed by identifying quality and essence of each research article, synthesizing the essence of whole research article to reflect a larger picture of research on educational technology, and discussion of recommendations. There are 34 published research articles divided into 16 articles of 2016, 2 articles of 2017, 14 articles of 2018 and 2 articles of 2020. All of 34 research articles submitted for publication can be summarize results into 9 issues. The body of knowledge gained from research articles which is a body of knowledge on educational technology.